Effect of coagulant type and level on the properties of half-salt, half-fat Cheddar cheese made with or without adjunct starter: Improving texture and functionality. (December 2017) - McCarthy, Catherine M.; Wilkinson, Martin G.; Guinee, Timothy P.
Abstract: The potential of increasing proteolysis as a means of enhancing the texture and heat-induced flow of half-fat, half-salt Cheddar cheese made with control culture (CL, Lactococcus lactis subsp. cremoris/lactis ) or adjunct culture (AC, CL +  Lactobacillus helveticus ) was investigated. Proteolysis was altered by substituting bovine chymosin (BC) with camel chymosin (CC), or by a 2.5-fold increase in level of BC. In cheese with CL-culture, increasing BC led to a large increase in pH and more rapid degradation of αS1 -casein during maturation, and cheese that was less firm after 180 d. In contrast, substitution of BC with CC in cheeses made with CL-culture had an opposite effect. While chymosin type and level had a similar influence on αS1 -casein hydrolysis in the AC-culture cheeses, it did not affect texture or flowability. Grading indicated that cheese made with AC-culture and with a higher level of BC was the most appealing.